Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11003-017-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrogen on the Wear Resistance of Materials in the Friction Couples of Braking Units

Abstract: We describe a method for the industrial investigation of the friction couples of band-block brakes of drill winches preventing hydrogen release from the steel surface of the pulley rim by the electric field with like positive charges restricting the motion of hydrogen ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…The results of the study prove the findings of earlier scientific research [9,[20][21][22][23][24][25][26], regarding the positive use of carbon nanoparticles of different shapes as "additives" and friction modifiers to lubricants. However, it should be noted that in papers [4,5,8,25], there were used the pure forms of carbon, mainly fullerenes, the cost of obtaining of which is by an order of magnitude higher than that of obtaining conglomerate of carbon of this study.…”
Section: Discussion Of Results From Studying the Influence Of Concentsupporting
confidence: 84%
“…The results of the study prove the findings of earlier scientific research [9,[20][21][22][23][24][25][26], regarding the positive use of carbon nanoparticles of different shapes as "additives" and friction modifiers to lubricants. However, it should be noted that in papers [4,5,8,25], there were used the pure forms of carbon, mainly fullerenes, the cost of obtaining of which is by an order of magnitude higher than that of obtaining conglomerate of carbon of this study.…”
Section: Discussion Of Results From Studying the Influence Of Concentsupporting
confidence: 84%
“…It was previously found that for the formation of a polymer matrix with improved physical and mechanical properties, the following components should be used in As it is known [5,12], a significant effect in improving the CMs properties is observed when introducing nanofillers in homeopathic doses. At the initial stage, the effect of the content of the ONA nanofiller on the elasticity modulus during bending of epoxy-polyester CMs was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in requirements is conditioned by the reliability of parts and mechanisms by reducing failure probability, their durability and reducing the inter-repair operational period [7][8][9][10]. Nowadays, polymers are the most widely used structural materials that are replacing metals and alloys [11][12][13]. The use of polymeric materials instead of metals increases the cost-effectiveness, reduces manufacturing costs and the weight of parts, with saving the physical-mechanical and thermophysical properties [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, an increase of particle size contributes to a decrease of heat transfer coefficients. In addition, during heat transfer in systems with nanofluids, the volume concentration of nanoparticles and their thermal conductivity coefficient have the main effect [35,53,77,84,89,95,114,132,150,158].…”
Section: Behavior Of Nanoparticles In the Engine Cylinder Head Cooling Systemmentioning
confidence: 99%